Implementation of Local Regulation of Batam City Number 1 of 2019 on the Arrangement and Empowerment of Street Vendors in the Perspective of Fiqh Siyasah Dusturiyah (Case Study of Sagulung District, Batam City) - Salsa Angreini; Khalid (Warmadewa Press, 2024)
Street sellers bring good and harmful community turmoil. These conflicts are common in Indonesia, especially in cities like Batam, where they have created several obstacles to people's activities, such as difficult access for pedestrians who have to pass through areas or trading locations that are very crowded with street vendors' stalls and carts and many vendors' locations, making it difficult for people, especially pedestrians, to walk to their destination. Street vendor facilities are damaged and inoperable, limiting public access. Batam City Regional Regulation Number 1 of 2019 on the Arrangement and Empowerment of Street Vendors in the Review of Fiqh Siyasah Dusturiyah (Case Study of Sagulung Subdistrict, Batam City) is examined in this study This field study uses qualitative descriptive analysis. Data are described, examined, and discussed to answer the problem. Purposive sampling was utilized to find informants in this study. This study found that the Local Regulation of Batam City Number 1 of 2019 on the Arrangement and Empowerment of Street Vendors in the Review of Fiqh Siyasah Dusturiyah (Case Study of Sagulung District, Batam City) has not been implemented. Unimplemented empowerment involves business capabilities, finance access, trade facility support, institutional enhancement, production growth, processing promotion networks, and technical help. Second, Siyasah Dusturiyah claims that the Islamic Law Review of the Implementation of Batam City Regional Regulation Number 1 of 2019 concerning the Arrangement and Empowerment of Street Vendors in Sagulung District, Batam City violates the General Principles of Good Governance, Social Balance, and State Responsibility